Integrating single-cobalt-site and electric field of boron nitride in dechlorination electrocatalysts by bioinspired design - Min, Yuan; Zhou, Xiao; Chen, Jie-Jie; Chen, Wenxing; Zhou, Fangyao; Wang, Zhiyuan; Yang, Jia; Xiong, Can; Wang, Ying; Li, Fengting; Yu, Han-Qing; Wu, Yuen (Nature communications, 2021)
The construction of enzyme-inspired artificial catalysts with enzyme-like active sites and microenvironment remains a great challenge. Herein, we report a single-atomic-site Co catalyst supported by carbon doped boron nitride (BCN) with locally polarized B–N bonds (Co SAs/BCN) to simulate the reductive dehalogenases. Density functional theory analysis suggests that the BCN supports, featured with ionic characteristics, provide additional electric field effect compared with graphitic carbon or N-doped carbon (CN), which could facilitate the adsorption of polarized organochlorides. Consistent with the theoretical results, the Co SAs/BCN catalyst delivers a high activity with nearly complete dechlorination (~98%) at a potential of −0.9 V versus Ag/AgCl for chloramphenicol (CAP), showing that the rate constant ( k ) contributed by unit mass of metal ( k /ratio) is 4 and 19 times more active than those of the Co SAs/CN and state-of-the-art Pd/C catalyst, respectively. We show that Co single atoms coupled with BCN host exhibit high stability and selectivity in CAP dechlorination and suppress the competing hydrogen evolution reaction, endowing the Co SAs/BCN as a candidate for sustainable conversion of organic chloride. Bridging the biocatalytic repertoire and the effective environmental remediation remains a great challenge. Here, inspired by the dehalogenases, the authors designed a single atom Co catalyst on carbon doped boron nitride that exhibits high stability and selectivity in dechlorination.